Relay Feedback Analysis for Double Integral Plants - Zhen Ye; Qing-Guo Wang; Chong Lin; Chang Chieh Hang; Andrey E. Barabanov (Journal of Control Science and Engineering)
Double integral plants under relay feedback are studied. Complete results on the uniqueness of solutions, existence, and stability of the limit cycles are established using the point transformation method. Analytical expressions are also given for determining the amplitude and period of a limit cycle from the plant parameters.